Kebijakan Dividen Pada Perusahaan Sektor Industri Barang Konsumsi di Indonesia: Kebijakan Utang, Profitabilitas, Likuiditas - Nurlatifah Asikin; Samtri Dortua Gultom; Amrie Firmansyah (Universitas Matana, 2021)
This study aims to investigate the effect of debt policy, profitability, and liquidity on dividend policy. This study uses secondary data sourced from companies' annual financial statements. The data source in the form of financial reports is obtained from the official website of the Indonesia Stock Exchange with the page http://www.idx.co.id. Based on purposive sampling has been conducted, the total sample used in this study amounted to 63 observations. Hypothesis testing uses panel data regression. The study suggests that debt policy, profitability, and liquidity do not affect dividend policy. Therefore, the information from these three variables cannot be used as a signal in predicting the company's dividend policy. This research indicates that the information on the level of debt, net income, and the amount of cash in the financial statements is not employed by investors in assessing the company's dividend policy.